Предмет: Математика,
автор: белка108
как решить (2-х)+3(х-3)=-13
Ответы
Автор ответа:
0
(2-x)+3(x-3)=-13
2-x+3x-9=-13
-x+3x=-13+9
2x=-4/2
x=-2
2-x+3x-9=-13
-x+3x=-13+9
2x=-4/2
x=-2
Автор ответа:
0
(2-х) + 3- 0=-13
2-х+3х=-13
-х+3х=-13-2
2х=-15
х=-7.5
2-х+3х=-13
-х+3х=-13-2
2х=-15
х=-7.5
Похожие вопросы
Предмет: Другие предметы,
автор: mashenkovgleb
Предмет: География,
автор: piontkevichdenis
Предмет: Другие предметы,
автор: solodilovavarvara28
Предмет: Математика,
автор: romanarutiunov
Предмет: Литература,
автор: tatieva97